STRЕSS-STRАIN STАTЕ ОF SОIL DАMS UNDЕR THЕ АСTIОN ОF STАTIС LОАDS - Usmonxo'jayev, Sanjar; Mаtkаrimоv Paxridin; Jurаеv Donyor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The objective of this article is to develop a methodology for the static calculation of earth dams under the action of water pressure in the reservoir, taking into account various physical and mechanical characteristics of soils, and the design features of the Pachkamar, Gissarak, and Sokh earth dams in a two-dimensional statement.